PENGENALAN KONSENTRASI WARNA PELUMAS MENGGUNAKAN WEBCAM - Winarno Winarno; Deny Arifianto; Sisca D N Nahdliyah; M Z Pratama; R A Nuswantari (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
The number of fake lubricants in Indonesia has made many people nervous. In 2008, 50% to 60% of lubricants that already existed in Indonesia were fake, therefore carefulness was needed in choosing these lubricating products. The first step that can be done to identify fake lubricants is to recognize by its color. Therefore, this research aims to design a device that is able to recognize the color of lubricants using a webcam. The research sample is base oil with levels of red and blue, each of which is 0 ppm, 10 ppm, 50 ppm, 100 ppm, 150 ppm, and 200 ppm. This sample is characterized by the color composition used as a reference system, then tested to identify other samples. Characterization is done by placing a sample on a cuvette and inserting it into the sample room with adequate lighting. The web camera is used to take sample pictures, then the image is analyzed based on color composition. Based on the results of tests that have been conducted, it shows that this system is able to identify 100% lubricant samples correctly. These results indicate that it is very possible to develop an early detection method for lubricating oil based on the composition of the colors using a webcam.